Brain Gain Of Corporate Board And Firm Performance: Evidence From Malaysia - Chuah, Shu Fen (2019)
Despite the importance of brain gain to alleviate brain drain issues and to fulfil the demand of human capital in Malaysia, current research on brain gain does not sufficiently reflect the brain gain situation in Malaysia and its financial impact brought is not evident. While there is abundance of research on brain gain issues from human resource and strategic management context, little has viewed it from corporate finance perspective, owing primarily to privacy reason and capacity of brain gain data. As Malaysia is an emerging country, corporate sector remains the main driver of economic growth. The growing of corporations need to be supported and led by talented company board and management. Using the sample of 803 firms from 10 industries in Bursa Malaysia’s Main Board from year 2009 to 2015, this study examined the impacts of the presence of brain-gain director on firm performance. Two-step robust GMM estimation result showed that for every additional number of brain-gain director on board, we can expect firm performance to increase by an average of 4.55%, holding others constant. As brain-gain director is made up of foreign director and returnee director, analysis is repeated for these two groups. It is shown that, for every number of foreign director and returnee director increased on board, firm performance is expected to increase by an average of 7.41% and 3.23% respectively. It is also found that board meeting attendance and the presence of family director do not affect the relationship between the presence of brain-gain director and firm performance.